NANOFIBRILLATED CELLULOSE, THE SMALL PROMISING FIBER: CHARACTERISTICS AND POTENTIALITIES - Silva, Eliane Lopes da; Vieira, Helena Cristina; Santos, Joielan Xipaia dos; Saul, Cyro Ketzer; Nisgoski, Silvana; Muñiz, Graciela Inés Bolzon de (Floresta, 2019)
Cellulose: an abundant, biodegradable and renewable plant material that is available all around the globe, from which nanofibrillated cellulose (a homogeneous suspension of fibers with nanometer-scale diameters) can be extracted. The nanofibrillated cellulose, in what concerns its range of application, may completely or partially replace other materials due to its particular physical properties. Knowing its characteristics and properties is important in understanding its behavior in various applications. In light of this remarks, the objective of this research was to extract the nanocellulose from bleached eucalyptus pulp through mechanical milling to characterize the resulting nanofibrillated cellulose and compare both. The nanofibrillated cellulose presented a very distinct appearance in relation to the original cellulose pulp when they were analysed in the same concentrations, demonstrating greater water absorption and fibrillar interweaving. The nanofibrillated material showed different responses in comparison to the original in terms of dimensions, thermal stability, crystallinity, viscosity, and degree of polymerization. The nanofibrillated cellulose displays the same chemical composition through infrared analysis and has diameters of around 21.7 nm, smaller than the cellulose diameter of 11.4 μm. The nanofibrillated cellulose also exhibits lower thermal resistance: its decomposition temperature was about 20 ºC lower than that of the original cellulose pulp, and its crystallinity index has decreased. As for viscosity and degree of polymerization, there was reduction of 25% compared to the original material. The results presented hereby indicate that the nanofibrillated cellulose has unique features in relation to the original cellulose pulp, which supports its application as an alternative to existing materials.